Hubungan Tingkat Ekspresi Fibroblast Activation Protein (FAP) Terhadap Faktor Klinikopatologi Karsinoma Tiroid Papiler - Herlina; Heni Maulani; Nursanti Apriyani (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2021)
BackgroundPapillary thyroid carcinoma is the most common subtype among thyroid cancers. The interaction between cancer cells and tumormicroenvironment plays roles in cancer proliferation and invasiveness. One of important components of tumor microenvironmentthat could stimulate tumor proliferation and invasiveness is activated fibroblast, known as carcinoma associated fibroblasts (CAFs).The aim of this research is to analysed FAP expression is associated with clinicopathologic characteristics.MethodsThis retrospective descriptive observational study with serial cases design was conducted in 40 samples of the paraffin blocks oftissues registered in Department of Anantomical Pathology Faculty of Medicine University of Sriwijaya/Dr. Moh. Hoesin PalembangHospital from January 1st, 2017 to October 31st, 2019. All samples were immunostained with FAP antibody. The expressions of FAPwere evaluated in accordance with the results of the previous study. Statistical test was performed by using Chi-square andSpearman-rho statistical test. Statistical analysis was performed by using SPSS version 23.0.ResultsOur data indicated that patients who were ≥45 years old (21 cases; 52.5%), women (31 cases; 77.5%) suffered from this cancer themost. The stromal type found in ten classic, follicular, solid and columnar variance were pauci (25 cases; 62.6%), desmoplastic (8cases;20%), sclerosis (5 cases; 12.5%) and inflammatory (2 cases; 5%). The expression of FAP in tumor stroma has a significantcorrelation with histopathology subtypes (p=0.028) and stromal type (p=0.000).ConclusionFAP was expressed in tumor epithelial cells and fibroblast stromal tumour of papillary thyroid carcinoma. FAP expression in stromaltumor between histopathologic subtype and stromal type showed significant correlation